The discursive construction of identities by the 2017 Barcelona terrorists - Giménez García, Roser; Queralt, Sheila (Boletín de Filología, 2023)
The literature on jihadist discourse focuses on the processes of propaganda and recruitment and on their dissemination through digital media. On the first session of the trial for the Barcelona and Cambrils attacks of August 17 and 18, 2017 (known as 17A), three videos were screened in which some of the young men who would later become responsible for the attacks convey their intentions while manufacturing explosives. This study analyzes their interaction from the perspective of pragmatic linguistics and examines the identities that the young terrorists construct for themselves and for others through the analytical model put forward in Stamou (2018). The results of this analysis scrutinize the linguistic resources used by the speakers to construct identities for themselves and others, as well as the relations established between these and the ideologies that support their discourse. We conclude that the analytical tools applied in this study may become very relevant for the discoursive and linguistic profiling of alleged terrorists for forensic purposes.